2013
DOI: 10.1080/0312407x.2013.829510
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Balancing Competing Needs: Embedding Involuntary Treatment Within a Recovery Approach to Mental Health Social Work

Abstract: The recovery model of mental illness has become increasingly influential over the past two decades and while the synergies with social work are strong, there has been no examination of how social workers manage working within a recovery framework with involuntary clients in risk management-oriented settings. In this paper we report on a qualitative study with 10 mental health social workers exploring how such tensions are managed in everyday practice. While the social workers identified numerous dilemmas, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Thus, Paul attributed successful recovery to a worker’s ability to apply equal value to both dimensions of practice by balancing these competing needs against each other [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Thus, Paul attributed successful recovery to a worker’s ability to apply equal value to both dimensions of practice by balancing these competing needs against each other [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Others strongly resisted treatment and experienced their care as coercive and oppressive. This means that the provision of information about the ward rules, their treatment, and their ITO conditions, and encouraging patients to seek independent advocacy can be an important strategy (Bland et al 2009;Courtney & Moulding, 2014;Shepherd et al 2009). However, regardless of how participants experienced their involuntary hospital admission, they all spoke about how staff attitudes and behaviours had the potential to make difference to their experiences of the ITO and being admitted to hospital.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Some argue that risk aversion and involuntary treatment are inherently in opposition with recovery approaches, as involuntary care impacts on the ability to establish relationships, and has a potential negative impact on a person's long-term recovery (O'Hagan 2012). However, others argue that keeping a focus on recovery principles, such as valuing the lived experience and the healing potential of relationships, can offer a platform to resolve some of these tensions (Bland et al 2009;Courtney & Moulding 2014;Deakin Human Services 1999;Trotter 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that this refocusing of mental health social work will not lead to the end of the need for restrictions and deprivations of liberty but, it is argued, it will affect the process, impact, frequency and duration of these types of intervention. It is encouraging that, as Courtney and Moulding (2014) found, individual social workers can manage to retain a recovery focus even in the context of risk and involuntary intervention. For this to become the general approach of mental health services it will be necessary but not sufficient for this to be reflected in education, training and supervision within services.…”
Section: Resultsmentioning
confidence: 99%
“…Courtney and Moulding (2014) in their qualitative study of social workers reported that practitioners do find ways of managing the "seemingly antithetical orientations" (p. 215) of involuntary intervention and recovery but that further education and training was needed on these complexities. Recent initiatives in Australia offer the type of structured guidelines that can effect purposeful changes to practice.…”
Section: Recovery-based Approaches To Riskmentioning
confidence: 99%